Retracted Confessions in Nepal: A Critical Study of Judicial Treatment and Procedural Safeguards - Neupane, Alaka (NPRC Journal of Multidisciplinary Research, 2025)
Confession has historically been treated as one of the most powerful forms of evidence in criminal proceedings. However, when a confession is retracted, courts face the challenging task of assessing its voluntariness, reliability, and evidentiary weight. This research examines how retracted confessions are handled within the Nepalese criminal justice system exploring the tension between protecting defendants’ rights against coerced confessions and ensuring that justice is not undermined by false retractions. Drawing upon doctrinal research, psychological theories of confession, and Nepalese statutory requirements, the study evaluates whether current judicial approaches adequately safeguard suspects’ rights while balancing the needs of justice. The findings highlight procedural gaps, the risks associated with coerced or compliant confessions, and the importance of corroborative evidence. The paper suggests reforms aimed at improving the integrity of confession evidence in Nepal.